Detection of Illegitimate Access Point Using Machine Learning (International Journal of Engineering and Computer Science, 2021)
Wi Fi and hotspots give remote web climate. With the successive utilization of  these,  there  is  a  quick  increment of  dangers  to  remote   AP   (Access   Point).   Correctly   when ill conceived AP’s are utilized around affiliations, federal government there’s excessive chance to be assaulted by different viruses as well as hacking strikes. It is important to distinguish the illegitimate access points to stay away from data break. In this paper we have used RTT (Round Trip Time) informational collection to recognize legitimate and illegitimate access points   in remote  incorporated  climate  and  afterward  investigate  them utilizing the machine learning algorithm including SVM (Support Vector Machine), KNN (K-Nearest Neighbor) and Decision Tree classifier.